Songs of Tagore : philosophy, selected translations, paintings - Tagore, Rabindranath, 1861-1941.; Rahman, Md. Anisur (Muhammad Anisur) (Dhaka : Pathak Shamabesh, 1999)
Songs, without musical notation.
Includes bibliographical references (p. 137-139).
Keywords: Tagore, Rabindranath, -- 1861-1941 -- Translations into English; Songs, Bengali -- India -- Texts -- Translations into English